The role of mycoplasmas as an infectious agent in carcinogenesis - M. A. Galyamina; O. V. Pobeguts; A. Yu. Gorbachev (Успехи молекулярной онкологии, 2023)
The review presents data on studies of the role of mycoplasmas as infectious agents in carcinogenesis, as well as their participation in cancer drug therapy and the impact on the outcome of treatment. Mycoplasmas are of particular interest because they have unique abilities to readily attach to and enter eukaryotic cells, modulate their functional state, and induce chronic inflammation while evading the host’s immune system. The review will highlight the data confirming the increased colonization of tumor tissue by mycoplasmas compared to healthy ones, describe the molecular mechanisms by which mycoplasmas activate the expression of oncogenes and growth factors, inactivate tumor suppressors, promote NF-κB-dependent migration of cancer cells and modulate apoptosis, which results in abnormal growth and transformation of host cells. The review also presents data on the effectiveness of anticancer drugs in mycoplasmal infections.